The ins and outs of manioc diversity in Gabon, Central Africa: A pluridisciplinary approach to the dynamics of genetic diversity of Manihot esculenta Crantz (Euphorbiaceae) - (:unkn) unknown (My University, 2009)
This thesis addresses the mechanisms behind the secondary diversification of manioc (Manihot esculenta Crantz) in Africa. Manioc (cassava) is propagated clonally, by way of stem cuttings, but has maintained its sexual fertility. Sex enters the plant's cycle when farmers choose to incorporate self-sown 'volunteer' plants originating from true seeds into their stocks of clones. The major role played by sexual reproduction in the domestication and diversification of several vegetatively propagated crops has become increasingly recognized. Much less is known, however, of similar interactions between farming practices and the biological traits of the crops in their areas of introduction. Because manioc sexual reproduction is not of immediate use to farmers, knowledge of the plant's intimate biological traits is intricately linked to the relationship of farmers to the plant, and diversity, in turn, is dependent on this knowledge. In Africa, the relative contribution of each component (sexual and asexual) of the plant's reproductive biology thus depended greatly on farmers' intimate perception and valuation of diversity, which depended, in turn, on the processes through which African farmers have built their own folk ecological knowledge of manioc. The patterns of folk reasoning with respect to the management of manioc volunteers in African farming settings were examined through a series of village-level studies of traditional manioc farming systems in Gabon, central Africa. Combining ethnobotanical and population genetic studies of local nomenclature systems of manioc landraces, the role of small-scale farmers as the possible 'architects' of the crop's secondary diversification in Africa was explored through the comparative study of ten communities of manioc farmers in Gabon. Africa's complex history and multiplicity of cultures has played a major part in shaping the high diversity of manioc in Gabon, and results show that cultural diversity accounts in part
Keywords: African Research